Visualization of liquid water in a lung-inspired flow-field based polymer electrolyte membrane fuel cell via neutron radiography. (1st March 2019) - Cho, J.I.S.; Neville, T.P.; Trogadas, P.; Meyer, Q.; Wu, Yunsong; Ziesche, R.; Boillat, P.; Cochet, M.; Manzi-Orezzoli, V.; Shearing, P.; Brett, D.J.L.; Coppens, M.-O.
Abstract: Lung-inspired, fractal flow-fields hold great potential in improving the performance of polymer electrolyte membrane fuel cells (PEMFCs) by providing uniform gas distribution across the electrodes and ensuring minimum entropy production in the whole system. However, the inherent susceptibility of the fractal flow-fields to flooding renders their use inadequate at high humidity conditions. In-depth understanding of water management in lung-inspired flow-fields is indispensable for the implementation of alternative outlet channel geometries or engineered water removal strategies to alleviate flooding. Here, liquid water formation and transport across the lung-inspired and serpentine flow-field based PEMFCs are evaluated using neutron radiography. The results reveal a propensity to flooding in the interdigitated outlet channels of the fractal flow-field with N = 4 generations as a result of slow gas velocity and narrow channel dimensions, which leads to significant performance deterioration. Neutron images also elucidate the importance of ensuring a well-defined internal channel structure of the fractal flow-fields to prevent backflow of liquid water via wicking and capillary pressure build-up arising from the narrow inlet gas channels and hydrophobic gas diffusion layer. Highlights: Neutron radiographs are presented for the lung-inspired and serpentine flow-fields. A well-defined channel structure of the fractal flow-field is indispensable. Water removal strategies required to alleviate flooding in the fractal flow-field.